2009
DOI: 10.1186/1751-0147-51-22
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sedation with detomidine and butorphanol on pulmonary gas exchange in the horse

Abstract: Background: Sedation with α 2 -agonists in the horse is reported to be accompanied by impairment of arterial oxygenation. The present study was undertaken to investigate pulmonary gas exchange using the Multiple Inert Gas Elimination Technique (MIGET), during sedation with the α 2 -agonist detomidine alone and in combination with the opioid butorphanol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 29 publications
5
20
0
2
Order By: Relevance
“…We suggest that the marked reductions in cardiac output (cardiac output was less than the estimated total blood volume of the dog) affected the early disposition of dexmedetomidine to such an extent that the assumption of a maximum concentration reached immediately after intravenous administration should be rejected (i.e., incomplete early distribution within the central compartment). For example, Grimsrud et al (2009) reported a range of 1 to 6 min for the observed time to maximum concentration (T max ) of detomidine after intravenous administration to horses, which could be explained by cardiovascular effects (Nyman et al, 2009), comparable with the present study.…”
Section: Discussionsupporting
confidence: 89%
“…We suggest that the marked reductions in cardiac output (cardiac output was less than the estimated total blood volume of the dog) affected the early disposition of dexmedetomidine to such an extent that the assumption of a maximum concentration reached immediately after intravenous administration should be rejected (i.e., incomplete early distribution within the central compartment). For example, Grimsrud et al (2009) reported a range of 1 to 6 min for the observed time to maximum concentration (T max ) of detomidine after intravenous administration to horses, which could be explained by cardiovascular effects (Nyman et al, 2009), comparable with the present study.…”
Section: Discussionsupporting
confidence: 89%
“…53.4). In one of the authors' experience, anesthesia induced with a butorphanol, and detomidine protocol in Baird's tapirs results in a time-dependent elevation in PaCO2 and decrease in PaO2, which is consistent with the effects seen during sedation with these drugs in the domestic horse (Nyman et al 2009). Even in healthy animals, heavy sedation and general anesthesia frequently lead to a fall in the arterial partial pressure of oxygen (PaO 2 ).…”
Section: Maintenance Anesthesiasupporting
confidence: 54%
“…The position of immobilized, recumbent large animals can lead to both hypoventilation and ventilation-perfusion imbalances (Hall 1971;Nyman et al 2009) and affect physiologic and blood gas parameters (Morkel et al 2010). In lateral recumbency, dependent lungs become atelectatic, which leads to poor ventilation, whereas the upper contralateral lung, while having opportunity for good ventilation, has poor perfusion, with the overall effect leading to ventilation-perfusion imbalance or shunted perfusion.…”
Section: Discussionmentioning
confidence: 99%